Librarian Perceptions of the Implementation of the National Standards of Library in University of Diponegoro Library - Rahman, Satria Ibnu; Heriyanto, Heriyanto (Edulib, 2021)
This study aims to determine the librarian's perception of implementing the National Library Standard at the UPT Library of Diponegoro University, Semarang. This qualitative research method uses observation and interviews as data collection techniques. Interviews were conducted in a semi-structured manner and involved five informants. The data obtained were then analyzed using thematic analysis from the results of data analysis determined 4, namely, the application of the SNP, the function of the SNP, the constraints on the application of the SNP, and the evaluation of the SNP. The application of the SNP includes the development of collections, infrastructure, library materials processing, and staff. The function of the SNP is to improve the quality of collections, consideration of accreditation assessment, reference in management, and reference uniformity of library management in Indonesia. Obstacles to applying SNP are constraints in the management and constraints of library policy. The evaluation of the SNP includes the SNP adding a discussion on up-to-date virtual visits, detailed explanations regarding the addition of collections, coordination between PNRI and the Ministry of Research, Technology and Higher Education regarding the application of higher education SNPs, administrative discipline, and continuing to implement SOPs and guidebooks. The results of this study are helpful for university libraries that implement SNP and for libraries that plan to use SNP as a standard for library services in universities.